First year medical students’ learning styles and performance (2016-2017) at Universidad Nacional Mayor de San Marcos - Hoyos-Flores, Mirko Humberto (2018)
Introduction: The learning styles were studied decades ago because of their usefulness for the creation of strategies following the students’ profile, in different education levels and courses. The performance achieved is considered in order to evaluate the efficiency of the strategies. So far, there is not a study that relates the learning style with the academic performance. Objective: This study has its goal in the identification of the learning styles used by the first year medical students, according to their preference level, and the relation between the style and the academic performance. Materials and Methods: The sample consisted of 234 students that were taking the first year on 2016 and 2017. We applied the Honey-Alonso questionary in order to classify the participants by their learning styles as active, reflective, theoretical, and pragmatic. We calculated also the preference of each style and searched for the relation between them and the academic performance. Results: The participants were 19 years old in average. The predominant style was the reflective (70.19%), following the theoretical (13.94%), pragmatic (10.58%) and the active (5.29%). We evidenced the domain of two styles among 22 students and three styles in 3 students and we didn´t find any statistical relation between the styles and the performance. Conclusion: The reflective prevailed and had a moderate preference, the other styles had a very high preference. There is not relation between the learning styles and the academic performance.